Planeamiento estratégico y presupuesto en las micro y pequeñas empresas textiles del Emporio Comercial de Gamarra - Silva Torralva, Hans Jhordan (2020)
Objective: Determine the relationship between strategic planning and budgeting in Micro and Small Textile Enterprises of Gamarra's commercial emporium. Method: Quantitative, experimental, cross - sectional and correlational research. The sample size consisted of 65 Micro and Small Textile Enterprises. The collection technique was the survey and the instrument was the questionnaire. Spearman's correlation test was used to respond to hypotheses and objectives. Results: Micro and Small Enterprises reached a regular level in strategic planning (63.1%) and in its dimensions: Strategies formulation (75.4%), strategies implementation (60%) strategies evaluation (67.7%); also in the budget (46.2%). Besides, it evidence a significant direct relationship between the strategic planning (p=0,001, Rho=0,472) and the budget, just like the implementation dimension (p=0,001, Rho=0,489) and the evaluation dimensión (p=0,02, Rho=0,371); however, it was not found the relation with the formulation dimension (p=0,180, Rho=0,168). Conclusions: Strategic planning is directly and significantly related to the micro and small enterprises budget. It mean, the more appropriate the planning be, the more appropriate the budget will be.